El mono imitamonos - Armijo, Consuelo; Ruano, Alfonso (Madrid : Ediciones S.M., 2004)
This is a story about a monkey who imitated everyone. When he was separated from his mother and had to survive in a city full of people he madke friends with some children and their mother takes him in until his mother finds him and returns him to the jungle.
Keywords: Monkeys -- Fiction; Spanish language materials; Spanish language materials -- Fiction; Fiction